The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s11064-018-2679-4
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 in Brain Physiology and Pathophysiology: Evidence from Transgenic Animal Models

Abstract: Angiotensin-converting enzyme 2 (ACE2) is a protein consisting of two domains, the N-terminus is a carboxypeptidase homologous to ACE and the C-terminus is homologous to collectrin and responsible for the trafficking of the neutral amino acid transporter B(0)AT1 to the plasma membrane of gut epithelial cells. The carboxypeptidase domain not only metabolizes angiotensin II to angiotensin-(1-7), but also other peptide substrates, such as apelin, kinins and morphins. In addition, the collectrin domain regulates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
117
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 87 publications
(105 reference statements)
1
117
0
5
Order By: Relevance
“…In addition, loss of ACE2 in brain cardiovascular centers short of neuronal death may impair proper autonomic nervous system regulation of blood pressure and potentially respiration (52). The loss of ACE2 in the brain stem may facilitate an increase in sympathetic drive, alterations in the baroreflex, and exacerbation of hypertension (1,8,54). Reduced expression of ACE2 in the vasculature may also promote endothelial dysfunction and inflammation and exacerbate existing atherosclerosis and diabetes (9,34,42,45,56,59).…”
mentioning
confidence: 99%
“…In addition, loss of ACE2 in brain cardiovascular centers short of neuronal death may impair proper autonomic nervous system regulation of blood pressure and potentially respiration (52). The loss of ACE2 in the brain stem may facilitate an increase in sympathetic drive, alterations in the baroreflex, and exacerbation of hypertension (1,8,54). Reduced expression of ACE2 in the vasculature may also promote endothelial dysfunction and inflammation and exacerbate existing atherosclerosis and diabetes (9,34,42,45,56,59).…”
mentioning
confidence: 99%
“…SARS-CoV-2 can invade the cardio-cerebrovascular system and damage the nervous system, which has been reported in several articles [8][9][10][11][12][13][14]. Angiotensin converting enzyme 2(ACE2) is highly expressed in human tissues such as vascular endothelial cells, heart, liver, digestive tract, and kidneys [15][16]. Studies have found that ACE2 is an important target for SARS-CoV-2 infection in humans.…”
Section: Discussionmentioning
confidence: 99%
“…On February 18, the patient had a high fever with a body temperature of 39.6℃, Re-examination of the craniocerebral CT revealed that: post craniocerebral operation, intracranial gas was accumulated, a drainage tube was placed, part of the left frontal parietal temporal bone was missing, and the left temporal lobe, basal ganglia and radiative coronal area showed patchy high-density lesions, which were significantly reduced compared with the previous (2020- [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The center line structure was less offset to the right than before, highdensity shadows on both sides of the ventricle were slightly reduced compared to before.…”
Section: Case Reportsmentioning
confidence: 91%
“…We could detect Cltrn transcripts in brain (Figure c) and this is in line with the already described expression of ACE2 in the nervous system (Komatsu et al, ). ACE2 is a protein consisting of two domains; the N‐terminus is a carboxypeptidase homologous to angiotensin‐converting enzyme (ACE) and the C‐terminus is homologous to collectrin (Alenina & Bader, ). Additionally, CLTRN has been found in secretory vesicles and in proximity to vesicle/membrane fusion events in pancreatic β cells (Akpinar et al, ), and it binds to soluble N‐ethylmaleimide‐sensitive‐factor attachment protein receptor (SNARE), a protein complex involved in intracellular movement of vesicles and membrane proteins.…”
Section: Discussionmentioning
confidence: 99%